Electrodynamics in Organic Dimer Insulators Close to Mott Critical Point - Marko Pinterić; David Rivas Góngora; Željko Rapljenović; Tomislav Ivek; Matija Čulo; Bojana Korin-Hamzić; Ognjen Milat; Branko Gumhalter; Predrag Lazić; Miriam Sanz Alonso; Weiwu Li; Andrej Pustogow; et al. (Crystals, 2018)
Organic layered charge-transfer salts κ -(BEDT-TTF) 2 X form highly frustrated lattices of molecular dimers in which strong correlations give rise to Mott insulating states situated close to the metal-to-insulator phase boundary. The salts κ -(BEDT-TTF) 2 Cu 2 (CN) 3 and κ -(BEDT-TTF) 2 Ag 2 (CN) 3 have been considered as prime candidates for a quantum spin liquid, while κ -(BEDT-TTF) 2 Cu[N(CN) 2 ]Cl has been suggested as a prototypical charge-order-driven antiferromagnet. In this paper, we summarize and discuss several key results, including some not reported previously, obtained in search to clarify the competition of these two ground states. The origin of anomalous dielectric response found at low temperatures in all three salts is also discussed. We conclude by pointing out the relevant new insights into the role of frustration and random disorder in the suppression of magnetic ordering and formation of the spin liquid state.